The nature of practice - Hayes, W. (coachesinfo.com)
About the thesis that "Practise makes perfect" and what's necessary that this can come true. Contents: - The cognitive stage - The associative stage - The autonomous stage - Knowledge - Lesson Objectives and Planning - Practice Structure and Selection